The AEWake Model: An AI-Enabled Instructional System for Enhancing Executive Function and Islamic Growth Mindset in Early Learners - Budiarti, Erna; Solehudin, Rd. Heri; Rahayu, Balqis Shinta; Hariangwibawa, Elyasa; Priyanti, Nita (Universitas Nahdlatul Ulama Surabaya, 2025)
In today's era of digital transformation and artificial intelligence, executive function skills and adaptive character are crucial competencies for students to face complex future challenges. Teaching that integrates interactive media based on smart technology with a spiritual values ​​approach is seen as an effective and creative strategy to cultivate these skills from an early age. Although previous research has focused on basic digital literacy, evaluation of the impact of teaching that combines cognitive and spiritual aspects holistically is still limited. This study aims to develop and test the effectiveness of an instructional system based on the AEWake model through a smart puzzle barcode hijaiyah media designed to stimulate executive function while instilling an Islamic Growth Mindset. Using a Research and Development (R&D) method with an adapted development model, the study involved 90 early childhood children as test subjects. Data collection techniques were carried out through structured observations based on the AEWake instrument and digital documentation, which were then analyzed using inferential statistics to measure the media's effectiveness. The results showed that the use of this instructional media had a significant positive impact on improving children's directed attention, self-control, and cognitive flexibility. The findings revealed that digital scaffolding through interactive content was a key variable influencing learning success, while the use of recycled materials was shown to increase sensory comfort without reducing the effectiveness of the technology. It is concluded that the integration of AI-enabled technology and Islamic values ​​is able to support sustainable cognitive and character development in the PAUD environment.